Adaptasi Masyarakat Transmigran di Desa Batang Pane II, Kecamatan Padang Bolak, Kabupaten Padang Lawas Utara - Yuyun Trisna Yuningsih; Nurjannah Nurjannah (Universitas Negeri Medan, 2019)
This study aims to determine the history, driving factors, adaptation, social solidarity, and barriers faced by Javanese and Sundanese ethnic transmigrant communities in adapting in Batang Pane II Village, Padang Bolak District, North Padang Lawas Regency. This study used a qualitative descriptive study with the subject of Javanese, Sundanese, and indigenous ethnic transmigrant communities namely the Batak Angkola sub-community. The results of the study show that the history of their transmigration was a result of the general transmigration program of 1982 under the rule of President Suharto. The driving factor is because you want to improve your standard of living, and get a more prosperous life. The adaptation of the transmigrant community went well, as evidenced by the interaction and communication that took place between each ethnic group. The social solidarity that occurs, can be seen in various kinds of activities carried out jointly, collaborating with each other and establishing cohesiveness in the community. Barriers to adaptation to barren soil environments so that people cannot grow crops other than perennials at the beginning of transmigration. The obstacle in communicating is because each ethnic group has a different language. The conclusion is that transmigrant communities with indigenous people each adapt to each other. The adaptation process does not fully occur naturally, but has been programmed by the government with evidence of laying houses for transmigrants and indigenous people randomly.